PENENTUAN UMUR PETIK DAN PELAPISAN LILIN SEBAGAI UPAYA MENGHAMBAT KERUSAKAN BUAH SALAK PONDOH SELAMA PENYIMPANAN PADA SUHU RUANG - Budi Santosa; Gatut Suliana (BUANA SAINS, 2010)
Snack fruit var. pondoh is one of perishable horticultural product its shelf life at room temperature is about of 6-7 days. This fruit is categorized as non climacteric based on its respiration type. Snack fruit should be ripe before harvesting and during storage does not undergo further ripening process. It has high respiratory rate that caused fast senescence. This research was aimed to determine harvesting time to obtain good quality and long shelf life of snack fruit. Also, it was objected to elucidate the effect of wax coatingon quality changes during storage. The harvesting time of snack fruit was 5, 6 and 7 month after pollination. The observations consisted on phisico-chemical characteristics of snack fruit. Wax coating (10%) was used to protect the fruits during storage. Glucose, fructose, sucrose and tannin was determined after harvesting. The quality of snack fruits was assesed by panelists independently. The results showed that the best harvesting time of snack fruit was 6 months after pollination. Wax coating influenced the fruit quality and also could inhibit declining of sugar and tannin content of fruit. Wax coating could improve the quality of fruits during storage up to 2 weeks